An assessment of style classification and clarification of intellectual style concept [Stil sınıflamaları ve zihinsel stil kavramının niteliği üzerine bir değerlendirme1] - SARICAN, ELİF (Ankara University, 2017)
Style, is a continuously growing area with the personality-oriented studies featuring individual differences. Although there are common features between style models, there are also some differences in terms of style approaches and theoretical basis. Style classifications are mostly configured considering these similarities and differences. The fact that pretty much style dimensions were defined in the literature causes new controversies. Due to them, researchers make suggestions that can create solutions to the problems of the style area. Intellectual Style was emerged as one of these suggestions. The concept of Intellectual Style, which was emphasized in recent years, is a new concept and it is used to express all kind of styles. This review focused on style classification, where intellectual style concept was scrutinized. © 2017, Ankara University. All rights reserved.
Keywords: Cognitive styles; Intellectual style; Learning styles